Application of bamboo fibre composite in structural strengthening - Doh, Shu Ing; Lim, Kar Sing; Jolius, Gimbun; Chin, Siew Choo; Lim, S.P.; Tong, Foo Sheng (Construction Research Institute of Malaysia, 2019)
Fibre reinforced polymer (FRP) is the most commonly used for structural strengthening, however, it requires high energy consumption to manufacture and non-environmental friendly. Alternatively, natural fibres such as bamboo, which has a high tensile strength characteristics may be used. However, limited study on the use of bamboo fibre as external structural strengthening is available. This paper presents the application of bamboo fibre vinyl-ester composite plate (BFVCP) for the strengthening of reinforced concrete (RC) beams. In this study, fibre volume fraction ranging from 0% to 40% were considered. The effect of volume fraction on the flexural and tensile strength of the composite plate was evaluated through mechanical test. The structural behaviour of RC beams was tested to failure using a four-point bending. BFVCP were applied externally in the beam’s mid-span of the bottom soffit to study the structural strengthening in flexure. Results showed that the highest tensile strength of the specimen was obtained using the fibre volume fraction of 40%. Strengthening of RC beam using BFVCP successfully re-gained about 2% of the original beam structural capacity, when applied to the weakened beam in flexure along the tension zone. Strengthening by BFVCP has diverted the vertical cracks at the mid-span to the edge of the plate. Result from this study shows that BFVCP may be used for weakened beam external strengthening.